Considerations on salts used for density separation in the extraction of microplastics from sediments. (May 2021) - Cutroneo, Laura; Reboa, Anna; Geneselli, Irene; Capello, Marco
Abstract: Environmental contamination by plastics and microplastics is a recognised problem worldwide, and it is the focus of many research teams. In the quantification of microplastics in the environment (plastic items with dimensions between 1 μm and 5 mm), the search for shared and universally recognised protocols and methodologies is still ongoing. In this study, the use of a method for extracting microplastics from marine sediments based on density separation has been considered. Fifty studies were analysed to investigate the scenario of salts exploited during microplastic extraction. The most commonly used salts are NaCl (45.6%), ZnCl2 (19.3%) and NaI (17.5%). Considerations related to cost, availability, hazards of the salts and thus the repeatability of the related extraction method are reported. In light of the findings, NaCl remains the most readily usable, economical and effective salt for the extraction of microplastics from marine sediments. Highlights: Density separation is the most widely method used for extracting MPs from sediment. A globally agreed research method requires easy availability of materials. Salts used in MP density separation are often dangerous to humans and environment.